Distribution of heavy metals in seafloor sediments on the East China Sea inner shelf: Seasonal variations and typhoon impact. Issue 2 (April 2018) - Li, Yunhai; Lin, Yunpeng; Wang, Liang
Abstract: Based on concentrations and distributions of heavy metals, grain size and loss on ignition (LOI) in the seafloor sediments acquired during three surveys in winter and in summer (before and after typhoon Morakot) in the mud deposition center off the Fujian-Zhejiang coast, East China Sea, the seasonal and typhoon-induced variations of heavy metals in seafloor sediments are discussed. It is found that different concentrations of heavy metals occurred in seafloor sediments, but their distribution patterns were similar, gradually decreasing from near-shore to offshore. The distribution of heavy metals was correlated with grain size and LOI in seafloor sediments, which showed significant seasonal variations and typhoon's impact. Based on these results, a conceptual evolution model was built about the seasonal and typhoon's impact on the deposition environment of heavy metals, which has implications for understanding the migration, settling, and burial processes of heavy metals in the sea. Highlights: The distribution of heavy metals in surface sediments showed seasonal differences. Typhoon Morakot has significantly impact on the distribution of heavy metals. The distribution of heavy metals was controlled by grain size and LOI. The distributional variation of heavy metals was correlated with the marine dynamics processes.